2021
DOI: 10.1002/adma.202107346
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Synthesis of I‐Rich Lithium Argyrodite Glass–Ceramic Electrolyte with High Ionic Conductivity

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.202107346. The Li symmetric cell with the LPSI 1.4 -gc electrolyte demonstrates ultralong cycling stability over 3200 h at 0.2 mA cm −2 . LiCoO 2 /Li 6 PS 5 Cl/Li all-solid-state battery applying LPSI 1.4 -gc as the anode interlayer also presents prominent cycling and rate performance. This work provides a novel type of electrolyte with high ionic conductivity and stability against Li metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Both the asmilled LPSCl and LPSCl 1.5 demonstrate broaden peaks that belong to the cubic argyrodite phase with halo backgrounds, indicating that partially crystallized glass-ceramic electrolyte has been successfully synthesized by the ultra-fast ball milling process. [37,38] Subsequent annealing of the as-milled electrolytes will result in much more crystallized electrolytes, as indicated by the XRD patterns with high peak-background contrast ratios in Figure 1b,c. For the LPSCl, the XRD patterns are almost the same as the samples annealed at different temperatures, all of which exhibit pure argyrodite phase without any impurity (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Both the asmilled LPSCl and LPSCl 1.5 demonstrate broaden peaks that belong to the cubic argyrodite phase with halo backgrounds, indicating that partially crystallized glass-ceramic electrolyte has been successfully synthesized by the ultra-fast ball milling process. [37,38] Subsequent annealing of the as-milled electrolytes will result in much more crystallized electrolytes, as indicated by the XRD patterns with high peak-background contrast ratios in Figure 1b,c. For the LPSCl, the XRD patterns are almost the same as the samples annealed at different temperatures, all of which exhibit pure argyrodite phase without any impurity (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…as polymer electrolytes, have been widely developed for the preparation of ASS-LMBs. [4][5][6] Among them, sulfide solid electrolytes (SSEs) are the most suitable for applying in large-scale energy storage devices because of their ultrahigh ionic conductivity (≈10 −3 -10 −2 S cm −1 ) comparable to the current organic liquid electrolytes. [7,8] Especially, the inherently soft property of SSEs is conducive to forming an intimate solid-solid interface contact in ASSLMBs via simple cold pressing technology at room temperature, which avoids the complicated high-temperature sintering process and tremendously improves machinability, and thus SSEs are optimal candidates for use in ASSLMBs at present.…”
mentioning
confidence: 99%
“…6.04 P 0.98 Bi 0.02 S 4.97 O 0.03 Cl was successfully synthesized via the Bi, O co-doping strategy, which can satisfy the requirements to enable superior ASS-LMBs. It is confirmed that with appropriate Bi and O co-substitution, not only high ionic conductivity of 3.4 × 10 −3 S cm −1 at room temperature but also good air-stability of the optimized Li 6.04 P 0.98 Bi 0.02 S 4.97 O 0.03 Cl electrolyte could be achieved.…”
mentioning
confidence: 99%
“…In the field of Li–S batteries, it is widely reported that the S 0 can be reduced within the range 2.0–2.3 V. , Considering that the discharge cutoff voltage of LMROs is 2.0 V, we speculate that combining LMROs with sulfide electrolytes in ASSLIBs might mitigate the deterioration of the cathode–electrolyte interface and hence enable enhanced cycling stability. Among the various sulfide electrolytes, lithium argyrodite Li 6 PS 5 X (X = Cl, Br, I) is regarded as the most promising one for ASSLIBs due to its high ionic conductivity (10 –3 –10 –2 S cm –1 ), low cost, and favorable mechanical properties for processing. , Herein, for the first time, a practical ASSLIB is demonstrated, with LMROs as the cathodes and Li 6 PS 5 Cl (LPSCl) as the electrolyte. The electrochemical performance of LMROs is significantly improved by proper composition modulation to achieve high electronic and ionic conductivities.…”
mentioning
confidence: 99%